ANALISIS KINERJA KEUANGAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA TETEHOSI KECAMATAN MANDREHE KABUPATEN NIAS BARAT - Gulo, Ihsan Putri Hidayati; Saragih, Joana L.; Lumban Gaol, Romasi (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to determine the Financial Performance of the Tetehosi Village Government, Mandrehe District, West Nias Regency in 2018-2020 by using the Independence Ratio Analysis, Effectiveness Ratio, Efficiency Ratio and Activity/Harmony Ratio. Where the data collection technique used is descriptive technique, where the data processed in this study is the Village Budget Realization Report in Tetehosi Village. The results of this study indicate that the Financial Performance of the Tetehosi Village Government, Mandrehe District, West Nias Regency in 2018 The independence ratio is at a very low ability level, the effectiveness ratio is at the less effective ability level, the efficiency ratio is at the inefficient ability level and the activity/compatibility ratio is at the level of ability is not balanced. Whereas in 2019 the independence ratio was at a very low ability level, the effectiveness ratio was at an ineffective ability level, the efficiency ratio was at an inefficient ability level and the activity/compatibility ratio was at an unbalanced ability level. Then in 2020 the independence ratio is at a very low ability level, the effectiveness ratio is at a fairly effective ability level, the efficiency ratio is at a less efficient ability level and the activity/compatibility ratio is at a fairly balanced ability level. The Tetehosi Village Government must explore the potential of its village and take advantage of existing village potentials that can be managed and developed for the sake of the interests, survival and development of the village. Keywords : Financial Performance, Village Budget Realization Report, Independence, Effectiviness, Efficiency, Activity/Harmony